Stroke in patients with Covid-19: Experiencie in a national referral hospital in Peru - Rodríguez-Kadota, Liliana (2021)
Background: Stroke is one of the leading causes of mortality worldwide and the current COVID-19 pandemic has a great impact on the care of these patients. Aim: To describe the characteristics of patients with a cerebrovascular event in patients hospitalized with COVID-19 in the medical center with the highest hospital capacity in Peru. Material and Methods. We conducted a retrospective study and included patients older than 18 years hospitalized with the diagnosis of COVID-19 and stroke. Results. A total of 26 adults were included, the mean age was 69.8 years and the median time of admission was 24 hours. Mortality was high (42.3%) and was associated with age and respiratory compromise by COVID-19. The majority of survivors had a poor functional outcome. Conclusion. It is concluded that improvement in care processes is necessary in order to make an early diagnosis and timely treatment.